ANALISIS PENERIMAAN SISWA MAN 1 METRO TERHADAP PENGGUNAAN MEDIA SOSIAL DALAM PEMBELAJARAN BIOLOGI DI MASA PANDEMI COVID-19 - Halimah Sa'diah; Nasrul Hakim; Yudiyanto Yudiyanto; Suhendi Suhendi (Akademika : Jurnal Teknologi Pendidikan, 2022)
The purpose of this study was to find out how the use of social media and student acceptance of the use of social media in biology learning during the Covid-19 pandemic was. This research is qualitative research using the case study method. The research subjects were biology teachers and students of MAN 1 Metro. The instruments used are questionnaires and interviews distributed via a google form. Data analysis used Milles & Huberman interactive analysis technique. The results showed that the use of social media in biology learning during the Covid-19 pandemic helped students in learning. This was evidenced by the data obtained from 3 indicators of student acceptance of Perceived Usefulness (PU) student responses as much as 7% Strongly Agree, 33% Agree, 29% Neutral, 26% Disagree, and 5% Strongly Disagree, from the Perceived Ease of Use Perceived Easy of Use (PEOU) student responses as much as 22% Strongly Agree, 48% Agree, 19% Neutral, 9% No Agree, and 2% Strongly Disagree, and from Perceptions of Behavior to Continue Using Behavioral Intention to Use student responses are 8% Strongly Agree, 15% Agree, 29% Neutral, 30% Disagree, and 18 Strongly Disagree. From these results, it can be concluded that social media can be used as an alternative media in learning with conditions that do not allow face-to-face learning, especially during the Covid-19 pandemic.